1999
DOI: 10.1063/1.371669
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GaAs/AlGaAs heterojunction bipolar transistor devices using photoreflectance and photoluminescence

Abstract: Photoreflectance (PR) and photoluminescence (PL) techniques were used to characterize the AlGaAs/GaAs heterojunction bipolar transistor (HBT) wafers grown by molecular beam epitaxy (MBE). The line shape of the PR GaAs signal is closely related to the cleanliness of the MBE system. The Franz–Keldysh oscillations of the GaAs signal become sharper, well defined, and the oscillation amplitude increases slightly as the MBE system is cleaned up. The dc current gain of the HBT devices was observed to increase accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Very few reports are available on the liquid-liquid interface self-assembly of gold nanorods, which is one of the most efficient structures for SERS applications. [27][28][29][30][31] The challenges associated with the interfacial assembly of gold nanorod are mainly related to the destabilization and partial aggregation during surfactant exchange. 19,32 Cheng et al used sequential ''grafting to'' (ligand exchange) and ''grafting from'' (surface initiated atom transfer radical polymerization) reactions to synthesize amphiphilic gold nanorods with mixed polymer brushes that can spontaneously assemble into two-dimensional arrays at oil/water interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Very few reports are available on the liquid-liquid interface self-assembly of gold nanorods, which is one of the most efficient structures for SERS applications. [27][28][29][30][31] The challenges associated with the interfacial assembly of gold nanorod are mainly related to the destabilization and partial aggregation during surfactant exchange. 19,32 Cheng et al used sequential ''grafting to'' (ligand exchange) and ''grafting from'' (surface initiated atom transfer radical polymerization) reactions to synthesize amphiphilic gold nanorods with mixed polymer brushes that can spontaneously assemble into two-dimensional arrays at oil/water interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shen et al 3) estimated the surface Fermi levels in GaAs and AlGaAs from the FK oscillations. In recent years, the measurements of FK oscillations have been applied to the characterization of epitaxial layer structures of heterojunction bipolar transistors, [4][5][6][7] high electron mobility transistors [8][9][10][11][12] and so on. In the analysis of the electric field strength, we usually plot the positions of the extrema of the FK oscillations in the asymptotic region from the critical point energy according to the following equation that is derived from the asymptotic form of an electro-optic function: 13) h…”
Section: Introductionmentioning
confidence: 99%
“…Since the emitter-base junction is a MBE-grown AlGaAs-GaAs heterostructure, we would expect to exhibit values of ␤ comparable to those demonstrated in AlGaAs-GaAs HBTs (␤ ϳ20-100 for similar emitter-base structures and device sizes͒. 10,11 Our earlier studies have shown that wafer fusion at elevated temperatures promotes the diffusion of dopants across interfaces ͑to be published elsewhere͒. This ''cross diffusion'' could in turn reduce both nB and D nB , leading to a reduced value of ␤.…”
mentioning
confidence: 90%